(untitled) (American Journal of Islam and Society, 1992)
Almost one-third of the total population of Muslims in the world today lives as a "minority" in lands where people of other faiths, cTeeds and ideologies have administrative, political and legislative control. As a religious minority, these Muslims face certain difficulties and challenges in practising their own distinct way of life.’ This paper, based on a study of the Muslim community in the Canadian National Capital Region (CNCR) conducted in 1992, explores how the Muslim community in the CNCR has integrated itself into Canadian society and how it has sought to maintain its Islamic identity in terms of religious practice and belief. It will demonstrate the impact of Canadian social values and structure on the formation of the Islamic identity of Muslims living in Canada and will also examine some of the ways by which this identity is maintained. This will be achieved by examining previous work in the field, the sociohistorical development and socio-demographic characteristics of the Muslim community in Canada (in particular in the CNCR), and immigration factors. The methodology and techniques used, findings, and conclusions will also be discussed. Previous Work in the Field To date, there have been few studies on North American Muslim communities. Those that do exist have focused primarily on the Middle Eastern (i.e., Arab) communities in Canada and the United States. Many have discussed the processes of acculturation and assimilation, in addition to attempts to preserve the traditional values, of these communities. The results have indicated a negative correlation between Islamic observance and non-Islamic societies. Since previous inquiries did not focus on the ...